La influencia de los paradigmas científicos en la enseñanza de la geografía en su trabajo escolar cotidiano - Santiago Rivera, José Armando (2025)
The purpose of this article is to explain the influence of emerging scientific paradigms on the teaching of geography in everyday school work. Currently, given the complex environmental reality, the educational work of school geography should be developed with a human and social sense. Therefore, there is an interest in updating the educational processes of positivist pedagogical practice, as it transmits neutral geographic content without practical application. In this regard, the use of the epistemic foundations of constructivism and critical theory is recommended, as they enable the elaboration of knowledge through research. This situation led to the completion of a bibliographic review, whose references facilitated the analysis of the historical situation, positive science in the teaching of geography, and qualitative research in geographic teaching. In these reflections, positivism is challenged for proposing geographic determinism and describing the physical and natural features of the territory. Therefore, the challenge is to innovate school activities with the interpretive and critical study of community geographic situations, by activating research, empowering students, and encouraging critical thinking and critical awareness. The article concludes by proposing a renewal of geographic pedagogical practice with the didactic support of qualitative research and provides knowledge and practices that make this pedagogical option feasible.